Oxford Street, Magnolias in bloom, Rochester, N.Y. - (:unkn) unknown (The Rochester News Company, 2009)
Oxford Street travel north-south through some of Rochester's famous areas like "The Neighbourhood of the Arts" and the "Park Avenue" area. The centre isle of the street is lined with Magnolia trees in bloom and the ground is littered with the petals. The postcard is addressed to Mrs. A.H. Wilson, Bernardston, Massachusetts. Affixed to the postcard is a US 1 cent stamp, postmarked March 8th, 1906. postcard number 6520.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Postcards; United States; Cities and towns--United States--Rochester; Streets--United States; Magnolias--United States; 1906; Plants, Ornamental--United States